A Descriptive Analysis of Translation Methods Found in The Book of Ecclesiastes - Mario Pellondou (CV. Tirta Pustaka Press, 2026)
The aim of this research is to analyze the bible translation by using methods of translation theory by Newmark (1988). This research was a qualitative research that focused to analyze the Book of Ecclesiastes. Bible entitled New King James Version (NKJV) and Alkitab Terjemahan Baru 2 (2023) were the data sources used. It was published by The Indonesian Bible Society. The book consists of 12 chapters. Informal method was used to present the results of the analysis. It was the explanation of the translation methods used. Formal method was used to describe the table of the frequency of the translation methods applied in the bible translation found in the old testament bible of Ecclesiastes. The translation methods found in data source were word for word translation, literal translation, faithful translation, semantic translation, free translation, idiomatic translation, and communicative translation. Adaptation was not found in all chapters of data source. The most translation method applied in the old testament bible of Ecclesiastes was free translation. Free translation had the highest percentage in every chapter in the old testament bible of Ecclesiastes. In the other word, the translator tried to transfer the meaning from source text into target text with changing the form based on cultures in target language.